2009
DOI: 10.1073/pnas.0905234106
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 is an EGFR-regulated anti-apoptotic factor in lung cancer in never-smokers

Abstract: Fifteen percent of lung cancer cases occur in never-smokers and show characteristics that are molecularly and clinically distinct from those in smokers. Epidermal growth factor receptor (EGFR) gene mutations, which are correlated with sensitivity to EGFR-tyrosine kinase inhibitors (EGFR-TKIs), are more frequent in never-smoker lung cancers. In this study, microRNA (miRNA) expression profiling of 28 cases of never-smoker lung cancer identified aberrantly expressed miRNAs, which were much fewer than in lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
352
4
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(373 citation statements)
references
References 50 publications
11
352
4
6
Order By: Relevance
“…In our collection, however, we found significantly higher levels of miR-21 in early-stage tumors. This finding, together with the demonstration of miR-21 overexpression in experimental mouse lung cancers, suggests that miR-21 upregulation could be an early event in lung tumorigenesis, as it has also been suggested by a recent study showing that miR-21 is the most aberrantly increased miRNA also in lung tumors of never smokers (Seike et al, 2009). Further studies will be necessary to establish if individual variations in miR-21 expression could be a risk factor for the development of lung cancer in humans.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In our collection, however, we found significantly higher levels of miR-21 in early-stage tumors. This finding, together with the demonstration of miR-21 overexpression in experimental mouse lung cancers, suggests that miR-21 upregulation could be an early event in lung tumorigenesis, as it has also been suggested by a recent study showing that miR-21 is the most aberrantly increased miRNA also in lung tumors of never smokers (Seike et al, 2009). Further studies will be necessary to establish if individual variations in miR-21 expression could be a risk factor for the development of lung cancer in humans.…”
Section: Discussionsupporting
confidence: 73%
“…This is supported by the identification of networks targeted in thyroid reported here, showing that miR-21 in these cells could contribute to genomic instability, typical of advanced cancers. Conversely, miR-21 overexpression in lung could be advantageous preferentially in the early stages of tumor progression, as suggested by data indicating that in this cell type miR-21 is mainly involved in protection from apoptosis (Seike et al, 2009), which, in turn, is mainly critical in early stages of tumor development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seike et al [185] reported that miRNA microarray data showed higher levels of miR-21 in EGFR-mutant cases, and in vitro analyses using NSCLC cell lines showed that activated EGFR signalling upregulated miR-21 expression. A statistically significant positive correlation was observed between miR-21 expression levels and p-EGFR levels in NSCLC cell lines.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…26 A different profiles of miRNA expression was observed in lung carcinomas from never-smokers vs smokers. 27 Recent studies demonstrated that EGFR may be a functional target of miRNAs. 28,29 MiRNA-128, which is frequently deleted in lung cancers, directly downregulated EGFR, but did not correlate with EGFR mutation and prognosis.…”
mentioning
confidence: 99%